The Effect of Organic Semiconductor Electron Affinity on Preventing Parasitic Oxidation Reactions Limiting Performance of n-Type Organic Electrochemical Transistors - Alsufyani, Maryam (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.